The taxonomic status of Myotis aelleni Baud, 1979 (Chiroptera, Vespertilionidae) - Novaes, Roberto Leonan M.; Wilson, Don E.; Ruedi, Manuel; Moratelli, Ricardo (Zootaxa, 2018)
Myotis aelleni Baud, 1979 was described based on a large series from Chubut, Argentina, and is known only from the type locality and Río Negro, also in Argentina. According to the original description, M. aelleni is closest morphologically to M. chiloensis (Waterhouse, 1840), but can be distinguished based on the tricolored dorsal hairs and skull size and shape. The taxonomic status of M. aelleni has been questioned but the species is still treated as valid. Based on qualitative and quantitative analyses of the type series of M. aelleni, and series of M. chiloensis, including the neotype, we recognize M. aelleni as a junior synonym of M. chiloensis. M. aelleni and M. chiloensis have bicolor dorsal hairs and cannot be distinguished on the basis of the skull size and shape. After synonymy, M. chiloensis occur from Central Chile and western Argentina to central Patagonia and Tierra del Fuego archipelago. Twenty-one species of Myotis occur in South America, including Trinidad and Tobago.